2014
DOI: 10.1042/bj20131428
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol promotes degradation of the human bile acid transporter ASBT (SLC10A2)

Abstract: The sodium/bile acid co-transporter ASBT [apical sodium-dependent bile acid transporter; SLC10A2 (solute carrier family 10 member 2)] plays a key role in the enterohepatic recycling of the bile acids and indirectly contributes to cholesterol homoeostasis. ASBT inhibitors reportedly lower plasma triglyceride levels and increase HDL (high-density lipoprotein) cholesterol levels. RSV (resveratrol), a major constituent of red wine, is known to lower LDL (low-density lipoprotein) cholesterol levels, but its mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Recently, it was found that ASBT plays a key role in the enterohepatic recycling of BAs and indirectly contributes to cholesterol homoeostasis ( 26 ). RSV promotes the degradation of ASBT in vitro , which might have some clinical relevance with regard to the observed cholesterol-lowering effects of RSV ( 44 ). We found that RSV reduced ileal BA levels, with no effect on ASBT expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that ASBT plays a key role in the enterohepatic recycling of BAs and indirectly contributes to cholesterol homoeostasis ( 26 ). RSV promotes the degradation of ASBT in vitro , which might have some clinical relevance with regard to the observed cholesterol-lowering effects of RSV ( 44 ). We found that RSV reduced ileal BA levels, with no effect on ASBT expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although its function is best understood in the small intestine [45], SLC10A2 also is expressed in brain [46]. Resveratrol, a chief constituent of red wine, inhibits SLC10A2 expression and function through a Sirt1 (sirtuin 1)–independent manner [47]. Potentially an exciting therapy for LOAD, resveratrol reduces amyloid plaque pathology in AD animal models [48] and has been shown to be safe and well-tolerated in a large phase 2 LOAD clinical trial [49].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of intestinal Sirt1 down‐regulates dimerization cofactor of HNF1α, pterin 4α carbinolamine dehydratase 2/dimerization cofactor of HNF1α 2 (DCoH2)‐Hnf1α‐Fxr signaling and decreases hepatic BA levels as well as ileal BA metabolic genes, such as organic solute transporter α (Ostα), apical sodium dependent bile acid transporter (Asbt), and ileal bile acid binding protein . However, Sirt1 activator resveratrol degrades Asbt expression in vitro . Sirt1 increases hepatic Fxr messenger RNA (mRNA) expression, thus increasing Pgc1α/Hnf1α binding to the FXR promoter .…”
mentioning
confidence: 99%
“…(15) However, Sirt1 activator resveratrol degrades Asbt expression in vitro. (16) Sirt1 increases hepatic Fxr messenger RNA (mRNA) expression, thus increasing Pgc1a/ Hnf1a binding to the FXR promoter. (3) Sirt1 increases hepatic Fxr/Rxr heterodimerization at FXRE by deacetylating Fxr, primarily at Lys-217, and activates Shp and bile salt export pump (Bsep) mRNA expression.…”
mentioning
confidence: 99%